Gaya Pengambilan Keputusan Pembelian Pakaian Secara Online pada Generasi Z Indonesia - Santoso, Giovani; Triwijayati, Anna (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Strategic marketing decisions are based on the way the company understands consumers, including the way consumers make purchasing decisions. This study aimed to analyze the generation Z consumer decision-making style in Indonesia in the purchasing of clothing by online shop media. Generation Z is a generation that is different from the previous generation because it has a unique character and has technological literacy. In this reseach the decision-making style used eight factors from the Consumer Style Inventory (CSI). Samples of research were 200 people generation 16-22 years old who have bought clothes in online shop. The sampling technique used purposive sampling. Data analysis technique used the Confirmatory Factor Analysis. The results showed that seven factors that were brand consciousness, perfectionist, high-quality consciousness, recreational, hedonistic consumer, impulsiveness, confused by over choice, fashion-conscious novelty, and habitual and brand loyal orientation found in Indonesian Z generation in purchasing clothes by online. Another factor was that the price value of consciousness is not confirmed in this study. Understanding consumer decision-making styles can explain the basic considerations of Z generation as young consumers when choosing products from several alternative product choices, brand selection, online stores, and purchasing intentions.